Test preparation kit workbook TOEFL : test of English as a foreign language 2002-2003 - Ban biên dịch First News. (Tp.HCM : Nxb Trẻ, 2003)
This book helps you build the skills necessary to answer the questions on the TOEFL successfully. Also, it thoroughly familiarizes you with the TOEFL format and suggests test-taking strategies to help you improve your TOEFL scores.
Keywords: English language; Toefl; English language -- Study and teaching -- Textbooks for foreign speakers